PENGGUNAAN ALAT PERAGA BENDA KONKRIT MATEMATIKA SISWA KELAS III SDN 2 BUYUT UDIK - Yumi Sarassanti; Dwi Desmayanasari; Ruri Handayani (Universitas Muhammadiyah Lampung, 2025)
Mathematics is taught from elementary school onwards. However, not all students are able to follow this learning well, but many students cannot complete and master the mathematical concepts being taught, which means their learning outcomes are still below the KKM. The study focuses on the teacher's efforts to improve mathematics learning outcomes when the teacher does not complete the task completely, namely. H. learning is still teacher-centered. The purpose of this study was to improve student learning outcomes in learning mathematics in Fractions material by using concrete object props. The subjects of this study were teachers and students of SDN 2 Buyut Udik, Gunung Sugih District, Central Lampung Regency. The problems of this study are: low learning outcomes in mathematics from fractional material, teacher learning abilities must be improved again, teachers do not use the learning environment, learning is still teacher-centered resulting in low student scores. The type of research used is Classroom Action Research (CAR). The data collection technique was carried out by posttest. The results showed that 10 students (45%) of the 22 students achieved the KKM before using the Betoniobjekti teaching tool. After using concrete object visual aids in Cycle I the number of students who achieved the KKM increased to 17 students (77%), which was then continued in Cycle II with the results of students who achieved the KKM to 20 students (91 students).